Pelatihan kondisi fisik untuk pelatih cabang olahraga beladiri tarung derajat sumatera barat - Desi Purnama Sari; Yogi Setiawan; Liza Liza; Sari Mariati; Suci Nanda Sari; Anisa Sholiha Mia (Lentera Negeri, 2024)
The limited knowledge and understanding of the trainer about the importance of physical condition in the sport of Tarung Derajat is one of the indicators that determine the failure of a coaching and training process. The trainer's understanding of the aspects of good physical exercise is very much needed to be applied by every coach of Tarung Derajat martial arts to achieve maximum performance. The purpose of this activity is 1) to provide knowledge about the forms and methods of training used to improve the physical condition of fighters, 2) to increase knowledge in compiling a periodization of training programs 3) to provide knowledge in conducting tests and measuring the physical abilities of fighters in accordance with laws and principles. training based on applicable scientific principles. In the Tarung Derajat sport in West Sumatra, the sports facilities and infrastructure are adequate. What the local government has not done is coaching and providing training to trainers in an effort to improve their quality. Based on these situations and conditions, in order to spread the sport of Tarung Derajat as a sport of martial arts and national culture to all circles (the younger generation), it is necessary to develop the ability of coaches in the sport of fighting degrees. The stages in this training are 1) discussion, 2) training and 3) evaluation. The results of this activity provide increased knowledge and understanding of the Tarung Derajat martial arts coaches on the importance of physical condition and application in the preparation of training programs in Tarung Derajat martial arts and the trainers are able to evaluate athletes who have carried out the given training program